PELESTARIAN WARISAN BUDAYA KOTA LAMA PALOPO - AS, Chalid; Nur, Muhammad; Tahir Muda, Khadijah; Yusriana (JURNAL ILMU BUDAYA, 2023)
Palopo is one of three municipalities in South Sulawesi. The historical value of the city of Palopo radiates through the distribution of old buildings that we can still see today. Concentrated in the city space, which is currently known as the "Old City Area".  Palopo Old Town has slowly decreased its characteristics as a historical area. This paper is based on qualitative research. It highlights the preservation policy of the Old City of Palopo.  The preservation policy direction includes the dimensions of protection, potential development, and utilization. As for the direction of protection, namely, the need for control of space utilization to reduce the rate of damage and decrease the authenticity of the area and buildings, In addition, this area requires legal protection in the form of a designation as a Cultural Heritage Area. As for the development policy, this area can be directed to.